Synthesis and anti-HIV activity of conformationally restricted bicyclic hexahydroisobenzofuran nucleoside analogs - Díaz-Rodríguez, Alba (Org Biomol Chem, 2009)
A chiral synthesis of a series of hexahydroisobenzofuran (HIBF) nucleosides has been accomplished via glycosylation of a stereo-defined (syn-isomer) sugar motif 16 with the appropriate silylated bases. All nucleoside analogs were obtained in 52–71% yield as a mixture of α- and β-anomeric products increasing the breadth of the novel nucleosides available for screening. The structure of the novels bicyclic HIBF nucleosides was established by a single crystal X-ray structure of the β-HIBF thymine analog 22b. Furthermore, the sugar conformation for these nucleosides was established as N-type. Among the novel HIBF nucleosides synthesized, twenty-five compounds were tested as inhibitor of HIV-1 in human peripheral blood mononuclear (PBM) cells and seven were found to be active (EC(50) = 12.3–36.2 μM). Six of these compounds were purine analogs with β-HIBF inosine analog 22o being the most potent (EC(50) = 12.3 μM) among all compounds tested. The striking resemblance between didanosine (ddI) and 22o may explain the potent anti-HIV activity.